2019
DOI: 10.1159/000501073
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Asia-Pacific Colorectal Screening Score for Asymptomatic Participants and Outpatients in Northwest District of China

Abstract: Introduction: Asia-Pacific Colorectal Screening (APCS) score has been implemented for colorectal cancer screening in asymptomatic cohort in many regions. However, no study has validated its efficiency in Asian outpatients with mild-selflimited gastrointestinal symptoms yet. The purpose of this study was to validate its efficiency in asymptomatic subjects and outpatients in Ningxia. Methods: The records of 329 asymptomatic participants and 300 outpatients were collected and analyzed from database in the General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…The most important finding of this study is that the APCS score and its modified versions have certain ability to predict CAN in asymptomatic population in Xuzhou. This result is consistent with previous validation of the APCS score in Beijing [ 14 ] and Ningxia [ 15 ], which may mean that risk scoring scores can be used as a preliminary screening for colorectal cancer screening in China. Even more, as the updated Asia Pacific Consensus Recommendations on colorectal cancer screening recommended [ 11 ], the risk scoring system can select high-risk patients for colonoscopy and reduce the colonoscopy resource load required to detect one CAN.…”
Section: Discussionsupporting
confidence: 91%
“…The most important finding of this study is that the APCS score and its modified versions have certain ability to predict CAN in asymptomatic population in Xuzhou. This result is consistent with previous validation of the APCS score in Beijing [ 14 ] and Ningxia [ 15 ], which may mean that risk scoring scores can be used as a preliminary screening for colorectal cancer screening in China. Even more, as the updated Asia Pacific Consensus Recommendations on colorectal cancer screening recommended [ 11 ], the risk scoring system can select high-risk patients for colonoscopy and reduce the colonoscopy resource load required to detect one CAN.…”
Section: Discussionsupporting
confidence: 91%
“…An updated search confirmed an additional three eligible studies, resulting in a final sample of 13 studies included in the meta-analysis. [9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27] Study characteristics and quality assessment. Tables 1 and 2 summarize the characteristics and quality evaluation of the 13 included studies, all of which were conducted in the Asia-Pacific region.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 eligible studies were identified in this initial search. An updated search confirmed an additional three eligible studies, resulting in a final sample of 13 studies included in the meta‐analysis 9–13,17–27 …”
Section: Resultsmentioning
confidence: 99%
“…10 Currently, the CRN screening scoring system is mainly used to evaluate asymptomatic individuals, and there are few studies on symptomatic patients. 43,44 In the current study we aimed to develop a CRN risk score for patients with non-specific GI symptoms to optimize the allocation of colonoscopic resources. Compared to ACN, CRN has a higher detection rate during the colonoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%